PROFIL KEDWIBAHASAAN MAHASISWA BAHASA DAN SASTRA INGGRIS - Saunir, Saunir (English Department FBS UNP, 2008)
Nowadays, young people have shown different language phenomena in their daily conversations. It sems that they are not proud to use their mother tongues anymore. This article reports the results of a research done to the English students of FBSS UNP Padang to see the profile of their language use (their bilingualism profile) at the campus. The data show that Bahasa Indonesia is the first choice to use and the mother tongues, English and other languages follow.